Correction of psychological and neurological signs of alcohol hangover in rats with acetylcysteine - D. V. Kurkin; E. I. Morkovin; N. A. Osadchenko; L. P. Knyshova; D. A. Bakulin; E. E. Abrosimova; Yu. V. Gorbunova; I. N. Tyurenkov (Фармация и фармакология (Пятигорск))
The development of medications to treat alcohol hangover is important for a large number of people, especially those, who perform responsible and dangerous types of work. The severity of the hangover syndrome is determined by the toxic effect of acetaldehyde and its metabolic rate, which decreases with the depletion of glutathione, worsening and prolonging the hangover.The aim of the article is to provide an experimental basis for use of acetylcysteine as a precursor of glutathione in treatment of psychological, neurological and cognitive symptoms of ethanol hangover.Materials and methods. The study was performed in male Wistar rats. The ethanol hangover was modeled via an acute ethanol injection (i.p., 3 g/kg). After awakening, the animals were divided into 2 groups, receiving acetylcysteine (p.o., 1 mg/ kg) or saline. The intact group of the animals received saline only. Before and after acetylcysteine or saline administration, the animals were assessed according to Combs and D'Alecy scale. The adhesive test, the open field test, the passive avoidance test and Morris water maze test were also performed twice. The liver glutathione level was assessed in sacrificed animals. Results. The control group animals showed signs of neurological deficits and cognitive impairment, including a decreased locomotion, motor deficits and a memory decline. The rats administered with acetylcysteine after the ethanol intoxication, had a less severe impairment associated with an improved performance in the adhesive test, Morris water maze test and the passive avoidance test, and demonstrated an increased locomotion in the open field test. The liver glutathione content in the animals treated with acetylcysteine, was comparable to the glutathione content in the liver of the animals not exposed to the ethanol intoxication.Conclusion. Against the background of an acute ethanol intoxication, an oral administration of acetylcysteine in the rats, promoted an increase in liver glutathione levels and led to a decrease in severity of neurological and cognitive deficits in the animals.